ANALISIS NILAI-NILAI KEHIDUPAN PADA ANTOLOGI CERPEN: KOTA CERITA - Aprilya Siahaan; Odilia V. Simorangkir; Trisnawati Hutagalung (FKIP, Universitas Palangka Raya, 2023)
The purpose of this research is to analyze the values of life found in the short story anthology